Mechanism for the Distribution of Corporate Social Responsibility (CSR) Based on Government Regulation No. 47 of 2012 - Muhammad Taufiq Arrafi; Agustin Hanapi; T. Surya Reza (JURNAL RUANG HUKUM, 2026)
This study is motivated by the challenges in implementing Government Regulation No. 47 of 2012 concerning the Social and Environmental Responsibility of Limited Liability Companies, particularly the lack of clarity in supervisory mechanisms, weaknesses in sanction provisions, and the gap between national regulations and their practical implementation. These issues have reduced the effectiveness of Corporate Social Responsibility (CSR) as an instrument for sustainable development in Indonesia. This research employs a qualitative descriptive library research approach, drawing upon statutory regulations, books, peer-reviewed journal articles, and research reports published between 2020 and 2025. Data were collected through document analysis and examined using content analysis and descriptive qualitative analysis, supported by source and theoretical triangulation to ensure data validity. The findings indicate that Government Regulation No. 47 of 2012 comprehensively regulates the CSR distribution mechanism, including planning and budgeting by the Board of Directors with the approval of the Board of Commissioners or the General Meeting of Shareholders (GMS), the recognition of CSR expenditures as corporate expenses, and accountability and transparency through annual reporting, further reinforced by Minister of Law Regulation No. 49 of 2025. Nevertheless, significant weaknesses remain, particularly regarding the legal provisions governing responsible entities, the delegative nature of sanctions, and inconsistencies in the definition of CSR across different statutory regulations. The study concludes that although a legal framework for CSR has been established, its implementation continues to face structural challenges that require regulatory strengthening. The practical implications of this study include revising Government Regulation No. 47 of 2012 to incorporate explicit sanctions, harmonizing CSR definitions across relevant legislation, and strengthening the role of local governments through regional CSR regulations that integrate corporate CSR programs with regional development plans.